3D tissue formation by stacking detachable cell sheets formed on nanofiber mesh. (23rd March 2017) - Kim, Min Sung; Lee, Byungjun; Kim, Hong Nam; Bang, Seokyoung; Yang, Hee Seok; Kang, Seong Min; Suh, Kahp-Yang; Park, Suk-Hee; Jeon, Noo Li
Abstract: We present a novel approach for assembling 3D tissue by layer-by-layer stacking of cell sheets formed on aligned nanofiber mesh. A rigid frame was used to repeatedly collect aligned electrospun PCL (polycaprolactone) nanofiber to form a mesh structure with average distance between fibers 6.4 µ m. When human umbilical vein endothelial cells (HUVECs), human foreskin dermal fibroblasts, and skeletal muscle cells (C2C12) were cultured on the nanofiber mesh, they formed confluent monolayers and could be handled as continuous cell sheets with areas 3 × 3 cm 2 or larger. Thicker 3D tissues have been formed by stacking multiple cell sheets collected on frames that can be nested (i.e. Matryoshka dolls) without any special tools. When cultured on the nanofiber mesh, skeletal muscle, C2C12 cells oriented along the direction of the nanofibers and differentiated into uniaxially aligned multinucleated myotube. Myotube cell sheets were stacked (upto 3 layers) in alternating or aligned directions to form thicker tissue with ∼50 µ m thickness. Sandwiching HUVEC cell sheets with two dermal fibroblast cell sheets resulted in vascularized 3D tissue. HUVECs formed extensive networks and expressed CD31, a marker of endothelial cells. Cell sheets formed on nanofiber mesh have a number of advantages, including manipulation and stacking of multiple cell sheets for constructing 3D tissue and may find applications in a variety of tissue engineering applications.